2020
DOI: 10.1021/acs.est.9b07600
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Several Series of Cationic Surfactants in Rainbow Trout (Oncorhynchus mykiss) Following Exposure via Water

Abstract: Bioaccumulation assessment is important for cationic surfactants in light of their use in a wide variety of consumer products and industrial processes. Because they sorb strongly to natural surfaces and to cell membranes, their bioaccumulation behavior is expected to differ from other classes of chemicals. Divided over two mixtures, we exposed rainbow trout to water containing 10 alkyl amines and 2 quaternary alkylammonium surfactants for 7 days, analyzed different fish tissues for surfactant residues, and cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…In BCF experiments in the same aquarium facility with somewhat larger rainbow trout we measured a median k U of 266 L kg –1 d –1 for 10 neutral chemicals. 31 This lies well within the range measured for the cationic surfactants. Later in the paper we discuss the factors affecting k U from a mechanistic perspective.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In BCF experiments in the same aquarium facility with somewhat larger rainbow trout we measured a median k U of 266 L kg –1 d –1 for 10 neutral chemicals. 31 This lies well within the range measured for the cationic surfactants. Later in the paper we discuss the factors affecting k U from a mechanistic perspective.…”
Section: Resultssupporting
confidence: 84%
“…Since this was a research investigation and not a regulatory study, we modified the OECD protocol to suit the research questions, borrowing some elements of the BETTER BCF protocol. 31 Alkylamines, an important class of cationic surfactants (see Table S1 ), were chosen as the test chemicals. The log D MLW of alkylamines increases proportionally with alkyl chain length.…”
Section: Introductionmentioning
confidence: 99%
“…Apparent BCF values ranged from 0.1 to 1260 L/kg, hence came close but remained below the threshold of the B criterion of 2000 L/kg. The authors concluded that further studies with longer exposure time and smaller fish should be conducted on the bioaccumulative properties of cationic surfactants [35]. The 16 C alkyl amine that showed the highest bioaccumulation potential in that study is structurally similar to TMOA, which had the highest BMF of the six test substances.…”
Section: Earlier Screening Studies For Bioaccumulation Of Iocsmentioning
confidence: 85%
“…Kierkegaard et al [35] determined the tissue distribution of twelve cationic surfactants in rainbow trout (Oncorhynchus mykiss) following exposure via water. Rainbow trout were exposed for seven days to ten alkyl amines with chain length from 9 to 16 C and to two quaternary alkylammonium surfactants with 10 and 14 C-chains.…”
Section: Earlier Screening Studies For Bioaccumulation Of Iocsmentioning
confidence: 99%
“…The adsorption affinities of EDCs to GMs could be affected by solution chemistry in the real aquatic environment. It was reported that cationic surfactants have been widely used in industrial manufactures and personal care products [21][22][23][24][25][26], and the concentration in the aquatic environment, especially in waste water, could reach mg L -1 levels [22][23][24]. Thus, the coexisting cationic surfactant would affect the adsorption behavior of EDCs to GMs.…”
Section: Introductionmentioning
confidence: 99%